Analisis Flypaper Effect : Dampak PAD dan DAU Terhadap Kemandirian Keuangan Daerah Provinsi Sulawesi Selatan - Reski Pormadinah Imran; Halim Usman; Sultan Sultan (Universitas Muhammadiyah Purwokerto, 2026)
The Purpose of this study is to examine how Regional Original Revenue (PAD) and General Allocation Fund (DAU) affect Regional Finance Independence. Additionally, it seeks to determine whether the Flypaper Effect phenomenon is present among South Sulawesi Province’s district and city goverments between 2020 and 2024. There is a knowledge gap on the true effect of PAD and DAU on local fiscal autonomy, as evidenced by the conflicting findings of earlier studies on fiscal decentralization in indonesia about the connection between intergovernmental transfer and regional fiscal performance. Panel data regression analisis was used in a quantitative manner. The TKKD data base and the DJPK portal of the ministry of finance provided secondary data. In order to identifity the Flypaper Effect, the study was conducted in two stages : first, to ascertain how PAD and DAU affected regional spending; second, to evaluate their influence on regional financial independence. Greater local revenue improves fiscal capasity and lessens reliance on central transfer, according to the findings, which show that PAD has a positive and significant impact on regional financial independence. DAU, on the other hand, has a negligible and smaller impact on regional spending, indicating that payments from the federal government are becoming less important in influencing local fiscal policy. This study offers policy suggestions for enhancing local financial sustainability as well as actual proof of South Sulawesi’s increasing fiscal independence.